Learning Biostratigraphy in University of Diponegoro, Semarang - Lucky Agustina; Samuel Richard Natanael Simorangkir (Ikatan Ahli Geologi Indonesia, 2014)
Biostratigraphy is a branch of stratigraphy, which focuses on correlating and assigning relative ages of rock strata by using the fossil assemblages contained within them. In Diponegoro University, Semarang, Central Java Province, we learn biostratigraphy in micropaleontology subject, in the 5th semester. In total there are 6 months per semester and we get approximately 12 classes given by the lecturers and 10 other classes given by the lecturer assistants in the laboratory. In the class, there are 100 students, taught by 2 lecturers Mr. Hadi Nugroho, and Ms. Anis Kurniasih. They are the lecturer in paleontology, with master degrees. The lecturer assistants in the laboratory are our senior students who were interviewed and selected by the lecturers.